Participative Management of Employees in Decision-Making: An Empirical Study - Kumar, B. Ravi (International Journal of Business and Management Future, 2018)
Participative management of employees in decision-making is considered as a mechanism where workers have a say in the decision making process of an organization. In India WPM is an element of government labour policy. The concept behind this is to improve better relations among employees and workers. The present paper tries to explore about the workers participation in management in Visakhapatnam Steel Plant (VSP) by considering 604 respondent employees of steel plant in order to know their opinions regarding the above mentioned topics by using convenient sampling method, because VSP is big organization consisting of more than 20,000 employees (Both Permanent and Contract). All the employees are busy at their work and it will be difficult to collect the first hand information from the employees by using any other sampling methods except convenient sampling method.